Study of spectral and luminescent characteristics of wheat seeds after laser radiation - Zeinidenov, A.K.; Aimukhanov, A.K.; Mukametkali, T.M.; Ishmuratova, M.Yu.; Tleukenova, S.U. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The spectral and luminescent properties of wheat seeds were studied after laser radiation. The radiation of wheat seeds by monochromatic radiation was performed using a continuous semiconductor laser within the generation wavelength of λgen = 650 nm. The radiation power density in working area is 2.3 mW. The excitation and luminescence spectra of wheat seeds were measured. It was shown that after the radiation of wheat seeds by monochromatic radiation the luminescence intensity was increased to critical value. It has been established that radiation intensity of wheat seeds depends on the laser radiation time duration. The dependences of germination and sprout energy of wheat seeds from laser radiation time duration were studied. The dependences of luminescent intensity of wheat seeds correlate with germination and sprout energy data. The obtained results can be used for laser processing of wheat seeds of agricultural crops.
Лазер сəулесімен сəулелендірілген бидай дəнінің спектрлік-люминесценттік қасиеттерін зерттеу
Исследование спектрально-люминесцентных характеристик семян пшеницы после облучения лазерным излучением
Keywords: coherent radiation; luminescence; excitation spectra; irradiation; wheat seed; germination; sprout energy